The Relationship Between Initial Tender and Mini-Competition: EU and Lithuanian Perspectives on Framework Agreements - Andhov , Marta; Soloveičik , Deividas (Teisė, 2021)
The article conducts a comprehensive scholarly analysis of framework agreements – a public procurement technique often used across different European jurisdictions. Besides examining the general legal framework of the EU and Lithuanian law on framework agreements, the article also examines the newest EU case law. The authors analyse the relationship between the initial tender procedure establishing the framework agreement and the subsequent mini-competition that follows under the former to award the public contract. In contrast to the Lithuanian legal regulation and related case law, the authors argue that these two stages are interconnected and must be viewed as a unified part of the same procurement process in line with European legal doctrine. Finally, the article highlights the differences between framework agreements and public contracts.